miR-339-3p is a tumor suppressor in melanoma - Weber, Claudia; Luo, Chonglin; Hotz-Wagenblatt, Agnes; Gardyan, Adriane; Kordaß, Theresa; Holland-Letz, Tim; Osen, Wolfram; Eichmüller, Stefan B. (Cancer research, 2016)
Determinants of invasion and metastasis in cancer remain of great interest to define. Here, we report the definition of miR-339-3p as a novel tumor suppressive microRNA that blocks melanoma cell invasion without affecting cell survival. miR-339-3p was identified by a comprehensive functional screen of a human miRNA mimetic library in a cell-based assay for invasion by the melanoma cell line A375. miR-339-3p was determined as a strong inhibitor of invasion differentially expressed in melanoma cells and healthy melanocytes. MCL1 was defined as a target for downregulation by miR-339-3p, functioning through direct interaction with the 3′ untranslated region of MCL1 mRNA. Blocking miR-339-3p by an antagomiR was sufficient to increase melanoma cell invasion, an effect that could be phenocopied by RNAi-mediated silencing of MCL1. In vivo studies established that miR-339-3p overexpression was sufficient to decrease lung colonization by A375 melanoma cells in NSG mice, relative to control cells. Overall, our results defined miR-339-3p as a melanoma tumor suppressor, the levels of which contributes to invasive aggressiveness.